Academic Stress, Anxiety and Depression among the Students of Armed Forces Medical College, Dhaka Cantonment - Hossain, Molla Muntasir; Wahab, Md Abdul (Journal of Armed Forces Medical College, Bangladesh, 2016)
Introduction: Study in Medical College can act as a contributing factor in developing depression in medical students which may have possible negative academic and professional consequences. Study in any medical course is perceived as being inherently stressful across the globe. Studies on psychological problems such as academic stress, anxiety and depression among medical students have seen that these disorders are under diagnosed and under treated. In this background the present study was carried out with an aim to assess the magnitude of depression and its associated factors in medical students in AFMC. Objective: To find out the prevalence of depressive symptoms and its associated factors among the students of Armed Forces Medical College (AFMC), Dhaka, Bangladesh. Materials and Methods: This descriptive type of cross sectional study was carried out in AFMC, Dhaka, Bangladesh for a period from February to April 2014. A total of 211 students studying from 1styear to 4th year MBBS participated in the study. Depression was assessed by Goldberg’s General Health Questionnaire (GHQ-28) and Beck Depression Inventory(BDI) scoring was used to find out the level of depression. BDI scoring 0-10 was considered as normal ups and downs, 11-20 as mild depression, 21-30 as moderate depression, 31-40 as severe depression and more than 40 as extreme depression. Additional questions regarding socio demographic variables were also included. Data analysis was done by software SPSS 19 for windows. Results: A total of 211 students participated in the study. Among them 86(40.8%) students were reported as having mild to moderate depressive symptoms. Depression was very significantly (p<0.001) higher in 1st year 55(83.3%) than 2nd year 25(38.46%), 3rd year 03(5.45%) and 4th year 03(12%) students. Depression was significantly (p<0.05) higher in Non English Medium background 82(38.8%) than English Medium background 04(1.9%). Conclusion: Depression may be a significant hidden problem for few of the Medical students and mechanisms to identify and help students with mental health problems should be seriously considered. This calls for in-house counseling service and mentorship program at medical colleges for early detection and treatment of these problems that may help in the improvement of academic performance. Journal of Armed Forces Medical College Bangladesh Vol.12(1) 2016: 79-82